EFFEKTIFITAS OBAT HERBAL TERHADAP PENYEMBUHAN JERAWAT : A Systematic Review - Agus, Al Ihksan (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Acne is one of the most common skin diseases and usually affects almost everyone. Herbal remedies can be given to treat acne and do not cause side effects. The purpose of writing is to see the effectiveness of herbal remedies for healing acne. Methods: Recent literature reviews were conducted using the electronic databases of Pubmed, Wiley Online and Science Direct. The review method uses keyword terms and phrases of Herbal Medicine, Acne, and Facial Treatment. Results: From the results of 9 studies, it was found that there was anti-acne activity of herbal plants and was relatively safe because there were no severe side effects compared to conventional or synthetic treatments. And there is the effectiveness of herbal remedies for healing acne. Conclusion: Herbal plants have antioxidant, anti-inflammatory, antibacterial and anti-inflammatory effects. Some of the recommended plants based on journal reviews for treating acne include: Nigela Sativa L, Amurense Phellodendron, Tea Tree Oil, Mangosteen Fruit Skin, Aloe Vera, Lavandulla, Paper Murbey, Green Tea, Hops, Aloe Ferox, Punica Granatum (Pomegranate).